Pengaruh Lama Pemanasan terhadap Perkecambahan Benih Kelapa Sawit (Elaeis guineensis Jaqc.) - Habibi, Khusnan; Indrawati, Asmah (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
This article aims to analyze the effect of heating duration on the germination of oil palm seeds (Elaeis guineensis Jacq.) to determine the most effective heating period for improving seed viability. The problem is focused on the impact of different heating durations on germination rate and seed viability. To approach this issue, theories on germination physiology and seed dormancy breaking were used. Data were collected through an experimental method using a completely randomized design (CRD) with four heating duration treatments: 3, 5, 7, and 9 weeks, each with five replications. The results showed that the heating treatment significantly affected germination percentage, with a 5-week heating period producing the highest germination rate. This study concludes that heating within a specific duration can accelerate germination while maintaining optimal seed viability.